Why a Fetus Is a Human Person from the Moment of Conception : a Revisionist Interpretation of Thomas Aquinas? Treatise on Human Nature. - Payne, Craig (Edwin Mellen Press, 2010)
This work discusses Thomistic anthropology and natural law ethics, in relation to contemporary scientific knowledge. It presents the argument that human-ness and even personhood begins at conception. The ethical implications of this view are also considered.